2021
DOI: 10.1111/jrh.12614
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in digital access among American rural and urban households and implications for telemedicine‐based services

Abstract: Purpose To examine characteristics associated with disparities in digital access (i.e., access to high‐speed Internet via a computer or smartphone) in American rural and urban households given that digital access has a direct impact on access to telemedicine‐based services. Methods Using the 2019 American Community Survey, we analyzed the proportions of geographic area, race/ethnicity, and socioeconomic status according to device and high‐speed Internet access. Maximum likelihood logit estimators estimated how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 7 publications
2
39
2
Order By: Relevance
“…These findings corroborate previous studies demonstrating rural‐urban differences in access to broadband and underscore the importance of the continued inclusion of a broadband access objective in the recently finalized Healthy People 2030 7 . Our study complements older area‐level county‐ and ZIP Code‐level analyses by assessing broadband access on a more geographic granular level than previous area‐level studies and further exploring geographic variation by categorizing census tracts beyond dichotomous rural‐urban measures that have been used in older and recent individual‐level studies 7,18,19 . Using both a 4‐group categorization and a continuous measure of rural, we found that more isolated rural areas have the poorest access to broadband.…”
Section: Discussionsupporting
confidence: 83%
“…These findings corroborate previous studies demonstrating rural‐urban differences in access to broadband and underscore the importance of the continued inclusion of a broadband access objective in the recently finalized Healthy People 2030 7 . Our study complements older area‐level county‐ and ZIP Code‐level analyses by assessing broadband access on a more geographic granular level than previous area‐level studies and further exploring geographic variation by categorizing census tracts beyond dichotomous rural‐urban measures that have been used in older and recent individual‐level studies 7,18,19 . Using both a 4‐group categorization and a continuous measure of rural, we found that more isolated rural areas have the poorest access to broadband.…”
Section: Discussionsupporting
confidence: 83%
“…Nowadays, the opportunity to develop and deliver information virtually is increasing as well as its accessibility. It cannot be generalized that all American populations have access to internet-enabled devices and internet services since some minority groups and areas in the US might have limited access [91]. However, policies have targeted this population to help them access internet-enabled devices and internet services, giving them more opportunities through this digital era [92].…”
Section: Advantages Of the Virtual Program For Low-income Familiesmentioning
confidence: 99%
“…Furthermore, having no digital access was more frequent in nonmetropolitan households and in non-Latinx Black, Latinx, and Native American patients. 39 There is also a digital divide based on age, which could further exacerbate health disparities. In a study of patients ages 65 to 79, it was found that adults ages 70 years and older were significantly less likely to be registered to use patient portals than those ages 65 to 69 years, and across the entire study population, Latinx, Black, and Filipino patients were less likely to use patient portals, own a digital device (in those > 75 years of age), use the internet or email, compared with non-Latinx Whites and Chinese patients.…”
Section: The Role Of Technology In Communicationmentioning
confidence: 99%